Food neophobia and its relation with olfaction - Demattè, M. Luisa; Endrizzi, Isabella; Gasperi, Flavia (Frontiers in Psychology, 2014)
Food neophobia, that is the reluctance to try novel foods, is an attitude that dramatically affects human feeding behavior in many different aspects among which food preferences and food choices appear to be the most thoroughly considered. This attitude has an important evolutionary meaning since it protects the individual from ingesting potentially dangerous substances. On the other hand, it fosters an avoidance behavior that can extend even toward useful food elements. A strong link exists between food neophobia and both the variety in one person’s diet and previous exposures to different foods. In this review, the more recent findings about food neophobia will be concisely described. Given the suggested connection between the exposure to different foods and food neophobia, this review will focus on the relation between this attitude and human chemosensory abilities. Olfaction, in particular, is a sensory modality that has a central role in flavor perception and in food preference acquisition. Therefore, the latest evidences about its relation with food neophobia will be discussed along with the applied and cognitive implications.